2019
DOI: 10.1111/ejn.14526
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evidence consistent with an interaction between wild‐type and mutant SOD1 protein associated with canine degenerative myelopathy

Abstract: There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…The E40K mutation is the most frequently found mutation in DM-affected dogs ( 14 ). Previous studies have shown that cSOD1 E40K forms an enzymatically active dimer, which is prone to form aggregates in the spinal motor neurons of DM-affected dogs and cultured cells, indicating that the E40K mutation acquires toxicity as in hSOD1-linked ALS ( 15 , 16 , 17 ). In contrast, an experimental mutant, hSOD1 E40K , did not form aggregates in cultured cells, indicating that the E40K mutation induces species-specific aggregation of cSOD1 ( 15 ).…”
mentioning
confidence: 98%
“…The E40K mutation is the most frequently found mutation in DM-affected dogs ( 14 ). Previous studies have shown that cSOD1 E40K forms an enzymatically active dimer, which is prone to form aggregates in the spinal motor neurons of DM-affected dogs and cultured cells, indicating that the E40K mutation acquires toxicity as in hSOD1-linked ALS ( 15 , 16 , 17 ). In contrast, an experimental mutant, hSOD1 E40K , did not form aggregates in cultured cells, indicating that the E40K mutation induces species-specific aggregation of cSOD1 ( 15 ).…”
mentioning
confidence: 98%